Investing in early childhood nutrition - Ruel, Marie T.; Hoddinott, John F. (International Food Policy Research Institute, 2008)
It has long been known that good nutrition is essential to children’s physical and cognitive development, but recent evidence sheds new light on the optimal timing of interventions to improve child nutrition and the long-term effects of such interventions. Recent studies have shown that undernutrition has a whole range of effects that impede not only children’s nutrition and development in theshort term, but also their cognitive abilities and productivity in adulthood, with measurable economic impacts. They have also shown that the window of opportunity for addressing child nutritional needs in ways that produce healthy, productive adults lasts from conception through age two. After that, the effects of undernutrition are largely irreversible. By addressing the large and severe problem of early childhood undernutrition in many poor countries, policymakers could maximize the effectiveness of investments designed to achieve overall development goals.